2020
DOI: 10.3389/fonc.2020.572316
|View full text |Cite
|
Sign up to set email alerts
|

A Competing Risk Analysis Model to Determine the Prognostic Value of Isolated Tumor Cells in Axillary Lymph Nodes for T1N0M0 Breast Cancer Patients Based on the Surveillance, Epidemiology, and End Results Database

Abstract: Introduction: Knowledge of the association between isolated tumor cells (ITCs) in breast cancer patients and the outcome is very limited. We aimed to determine the prognostic value of axillary lymph node ITCs for T1N0M0 female breast cancer (FBC) patients. Methods: Data for T1N0M0 FBC patients staged ITCs negative [pN0(i−)] and positive [pN0(i+)] were extracted from the Surveillance, Epidemiology, and End Results database from 2004 to 2015. Prognostic predictors were identified by Kaplan-Meier analysis, compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The high tendency of lymphatic vascular invasion, lymph node involvement, as well as a high locoregional recurrence (LRR) risk were supposed to be aggressive clinicopathologic features of IMPC in the previous studies (25-28). Moreover, OS has always seemed as an unbiased measurement for survival prediction of breast cancer (13,14). In the current research, the 5-year OS for conservatively operated IMPC patients was 80.9%, which was slightly lower than 82.9%-90.0% in recent studies (15,16,28,29).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The high tendency of lymphatic vascular invasion, lymph node involvement, as well as a high locoregional recurrence (LRR) risk were supposed to be aggressive clinicopathologic features of IMPC in the previous studies (25-28). Moreover, OS has always seemed as an unbiased measurement for survival prediction of breast cancer (13,14). In the current research, the 5-year OS for conservatively operated IMPC patients was 80.9%, which was slightly lower than 82.9%-90.0% in recent studies (15,16,28,29).…”
Section: Discussionmentioning
confidence: 49%
“…As reported by previous studies (13)(14)(15)(16), the objective and reliable prognostic indicators, such as AJCC stage, age at diagnosis, and ER status, have always been seemed as the Variable selection by the LASSO binary logistic regression model. A coefficient profile plot was constructed against the log (lambda) sequence.…”
Section: Discussionmentioning
confidence: 93%
“…As reported by previous studies [11][12][13][14], the objective and reliable prognostic indicators, such as AJCC stage, age at diagnosis, and ER status, have always been seemed as the clinicopathological features which could direct clinical treatment for breast malignancies. In this study, based on the six risk factors affecting OS for IMPC patients undergoing BCS through multivariate Cox regression analyses, the nomogram suggested that AJCC stage contributed most to prognostic prediction, followed by age at diagnosis, ER status and PR status.…”
Section: Discussionmentioning
confidence: 95%
“…The high tendency of lymphatic vascular invasion, lymph node involvement, as well as a high locoregional recurrence (LRR) risk were supposed to be aggressive clinicopathologic features of IMPC in the previous studies [23][24][25][26]. Moreover, OS has always been seemed as an unbiased measurement for survival prediction of breast cancer [11,12]. In the current research, the 5-year OS for conservatively operated IMPC patients was 80.9%, which was slightly lower than 82.9%-90.0% in recent studies [13,14,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation